Enhancing Brand Image in the Digital Era: Evidence from Small and Medium-sized Enterprises (SMEs) in Indonesia - Tatik - Suryani; Abu Amar Fauzi; Mochamad Nurhadi (Gadjah Mada International Journal of Business, 2021)
This study aims to validate the essential antecedents of brand image enhancement in the digital era, based on a schematic theory. This study involved 400 respondents from four capital cities in Java, Indonesia, which comprise Surabaya, Jakarta, Bandung, and Yogyakarta, based on a quota sampling technique. The findings indicate that the quality of websites and social media sites may have no direct effects on brand image; any effects are transmitted through a serial mediation of brand awareness and E-WOM. Explicitly, the effect of a website’s quality on brand image is fully mediated, while social media’s quality effect on brand image is partially mediated through brand awareness and E-WOM. This study extends the current literature related to SMEs’ brand image. Also, this study offers practical recommendations for several stakeholders interested in empowering SMEs, including the government, entrepreneurship-based universities, and the SMEs themselves, who are all seeking strategies to enhance brand image while utilizing digital platforms such as social media and websites.